Pengaruh Komunikasi, Motivasi, serta Sertifikasi Guru Teradap Kinerja Guru - Purnamasari, Indah (Journal of Innovation in Teaching and Instructional Media, 2021)
The aim of this study is to examine further into effects of communication, motivation, and teacher certification in SMA Negeri Sekayu District, Musi Banyuasin District, both together and separately. The sample size for this quantitative study is 124 participants. The research instrument used primary and secondary data analysis in the form of questionnaires and teacher data, as well as documents relevant to research that were accessible in schools. The findings revealed that communication, motivation, and teacher certification all had a major impact on teacher performance in SMA Negeri Sekayu District, Musi Banyuasin District. Furthermore, communication has a partly positive impact on performance. This research is expected to be input for high school teachers in Sekayu District, Musi Banyuasin Regency. So that it can improve communication, work motivation, and teacher certification so that the performance of SMA Negeri Sekayu District, Musi Banyuasin Regency will be even better.